Pengembangan Sistem Point of Sale (POS) Berbasis Web pada Penjualan Merchandise K-Pop dengan Implementasi Framework Laravel - Dila Nur Sakinah; Zulva Al’Ilmi; M. Ilham Setya Aji; Abdullah, Abdullah; Muhamad Fikri (Journal of Science, Technology, and Innovation, 2025)
The development of a web-based Point of Sale (POS) system for Jayla Shop, an MSME engaged in K-Pop merchandise sales, aims to replace manual transaction recording and stock monitoring processes that can be inefficient and prone to errors. The system was developed using the Laravel framework with a MySQL database and the Waterfall development method, which includes requirement analysis, system design, implementation, testing, and evaluation. The system manages product data, stock data, sales transactions, and transaction details. Key features include automated sales transaction recording, transaction recap reports by specific periods, report export in PDF and Excel formats, an analytics dashboard with sales and product charts, best-selling product information, and stock notifications. In addition, the system supports receipt printing using a Bluetooth thermal printer. Functional testing was conducted using black-box testing and showed that all main features operated as expected, enabling the system to improve transaction efficiency and simplify report generation. Therefore, this POS application not only serves as a transaction support tool but also represents an initial step in the digital transformation of an MSME toward a more modern and integrated information system.